Maksimalisasi Zakat untuk Pemberdayaan Ekonomi: Strategi Pendampingan dan Manajemen yang Efisien - Sakum; Sukron Mamun; Ali Nur Ahmad; Kisanda Midisein; Listiyan Achmad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to explore the potential of zakat in empowering the economic community in Indonesia, with a focus on mentoring and efficient management strategies. Zakat, as an Islamic economic instrument, has strategic potential to overcome income inequality and promote economic equality. In Indonesia, with a majority Muslim population and cultural diversity, zakat is expected to significantly strengthen economic empowerment and community welfare. This research uses a qualitative approach involving observation, interviews and literature review. Field observations were carried out to understand the implementation of zakat in daily operations, while interviews with stakeholders such as entrepreneurs, zakat institution managers, and consumers provided in-depth insight into the challenges and opportunities in zakat management. A literature review was carried out to build a theoretical foundation and understand developments and policies related to zakat. Initial findings show that although zakat institutions in Indonesia have developed, the potential of zakat as an economic tool is not yet optimal because it is often considered a voluntary contribution. Optimizing zakat can be achieved through implementing the principles of good governance, integration in fiscal policy, and the use of digital systems for administration. Collaboration with other institutions is also important to increase transparency and accountability. It is hoped that this research can provide strategic guidance for the development and implementation of zakat as a more effective tool for economic empowerment, with a positive impact on reducing poverty and improving community welfare.